Genotype diversity and morphometric of tinfoil barb Barbonymus schwanenfeldii (Bleeker 1854) from Sumatera, Java, and Kalimantan - Deni Radona; Dinar Tri Soelistyowati; Odang Carman; Rudhy Gustiano (Jurnal Iktiologi Indonesia, 2016)
Study on genotype and phenotype diversity of initial population tinfoil barb from Sumatera, Java and Kalimantan is an effort to use genetic sources of tinfoil barb for sustainable aquaculture. This study was to evaluate the diversity of genotype and phenotype of tinfoil barb from Sumatra, Java and Kalimantan. Analysis of genotype diversity was con- ducted by RAPD methods using primer (OPA 08, OPA 09 and OPC 02) and phenotype based on truss morphometric measurement. The result showed that the highest genetic polymorphism (40%) was found in the male population of Java and female from Kalimantan with heterozygosity 0.18; while the lowest polymorphism was detected in the female population from Java (18%) with the heterozigosity level at 0.08. Based on the relationship between tinfoil barb from Java, Sumatera and Kalimantan by using three primer of RAPD showed that the genetic distance ranged from 0.48- 0.55, whereas between male and female population was ranged from 0.19-0.24. Canonical analysis using truss morpho- metric from 21 measured characters among three populations showed the different kind of genetic dispersion. From intrapopulation genetic sharing percentage, the highest interpopulation genetic sharing component was found in the tinfoil barb from Java (66.7-86.7 %), while interpopulation genetic sharing component ranged 0-6 % and 0 % were found in the tinfoil barb from Kalimantan and Sumatera, respectively. According to our results, the genotype diversity and phenotype of tinfoil male from Java and female from Kalimantan are genetic resources for developing tinfoil barb aquaculture. Abstrak Studi keragaman genotipe dan fenotipe populasi awal ikan tengadak (Barbonymus schwanenfeldii) asal Sumatera, Jawa, dan Kalimantan merupakan upaya pemanfaatan sumber daya genetik ikan tengadak untuk kegiatan budi daya secara berkelanjutan. Tujuan penelitian ini adalah melakukan evaluasi keragaman genotipe dan fenotipe ikan tengadak asal Sumatera, Jawa, dan Kalimantan. Analisis keragaman genotipe dilakukan secara molekuler dengan metode Random Amplified Polymorphism DNA (RAPD) menggunakan primer OPA 08, OPA 09 dan OPC 02 sedangkan keragaman fenotipe dilakukan berdasarkan pengukuran truss morphometric. Hasil penelitian menunjukkan polimorfisme genetik tertinggi (40%) ditemukan pada ikan jantan populasi asal Jawa dan ikan betina asal Kalimantan dengan nilai heterozi- gositas tertinggi 0,18 sedangkan polimorfisme terendah (18%) ditemukan pada ikan betina populasi asal Jawa dengan tingkat heterozigositas 0,08. Jarak genetik ketiga populasi berkisar 0,48-0,55 sedangkan antara ikan jantan dan betina berki-sar 0,19-0,24. Hasil analisis fungsi kanonikal truss morfometrik ikan tengadak pada 21 karakter terukur menun- jukkan sebaran pengukuran ketiga populasi berada pada kuadran yang berbeda. Persentase indeks keseragaman intra- populasi menunjukkan indeks keseragaman genetik tertinggi pada populasi Jawa (66,7-86,7 %) dengan indeks kesera- gaman interpopulasi (0-6%) pada populasi Kalimantan dan (0%) pada populasi Sumatera. Berdasarkan data keragaman genotipe dan fenotipe ikan jantan asal Jawa dan ikan betina asal Kalimantan berpotensi sebagai sumber genetik donor untuk pengembangan budidaya ikan tengadak.